(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Forearm bone fracture is a commonly encountered fracture. The inception of locking compression plate (LCP) has revolutionized fracture management. With their dramatic success for articular fractures, there is a speculation that they might be more appropriate for diaphyseal fractures as well. Objective: To compare internal fixation of closed, middle third forearm fractures with LCP and limited contact dynamic compression plate (LC-DCP) in adults with respect to union rate, implant failure, functional outcome, and infection rate. Methods: Twenty-two patients with closed, middle third fractures of both the forearm bones were involved in this prospective, randomized, controlled study, which took place between February 2019 to January 2021. They were segregated into two groups based on open reduction and internal fixation with LCP (n=11) and with LC-DCP (n=11). Postoperative follow-up intervals of 1, 2, 6 weeks and 3, 6 months. The patients were assessed for implant failure, fracture union and function outcome of Andersons’ criteria to assess union, forearm rotation, and wrist flexion-extension, and disabilities of the arm, shoulder and hand (DASH) score for patient related outcome at the latest follow up. Results: The mean age of the patients was 30.9 years (range 19-47 years) with mean follow up about of 2 years. The union rate in LCP group was (100%) whereas in LC-DCP was (81.8%), the p value was (0.4), which is not statistically significant. The p value for Quick DASH score and Anderson’ criteria were (0.8 and 0.43), respectively which is also not statistically significant. No incidence of implant failure in both groups. Conclusion: Although LCP is an effective treatment alternative and may have a subtle edge over LC-DCP in the management of these fractures, their supremacy could not be certified. We deduce that surgical planning and expertise rather than the choice of implant are more pivotal for outstanding results. Keywords: Limited contact dynamic compression plate, locking compression plate, closed, middle third fractures, both bones of forearm Citation: Chhaily ZA, Joda AI, Abd Ali AS, Ali ZH. Is locked compression plate better than limited contact dynamic compression plate in treatment of closed middle third radius and ulnar fractures in adults: A short-term comparative study. Iraqi JMS. 2022; 20(1): 146-153. doi: 10.22578/IJMS.20.1.19